Dimorfismo sexual y cuarto conducto del primer molar mandibular permanente con tomografía cone beam en consultorio de la práctica privada, Iquitos–2024 - Delgado Noriega, Carlos Johan (2025)
The objective of this study was to investigate the potential association between sexual dimorphism and the presence of a fourth canal in the permanent mandibular first molar (CCPMP). The sample consisted of 359 patients 204 females (56.8%) and 155 males (43.2%) who underwent cone-beam computed tomography (CBCT). The scans were obtained from the digital archive of a private dental practice in the city of Iquitos, Loreto, between 2018 and 2024. All tomographic images that met the established inclusion and exclusion criteria were included in the study. Axial, sagittal, and coronal tomographic sections were analyzed to assess the presence of the CCPMP, as well as the number of foramina and roots in the distal portion of the mandibular first molar. Statistical analysis was performed using SPSS version 27, applying Pearson’s Chi-square test with a significance level set at p < 0.05. The mean age of the study sample was 38.89 ± 16.28 years. The overall prevalence of the CCPMP was 16.7%, with 17.2% observed in females (35 of 204) and 16.1% in males (25 of 155), showing no statistically significant association with sex (p = 0.796). It is therefore concluded that no relationship exists between sexual dimorphism and the presence of a fourth canal in the permanent mandibular first molar.